2012
DOI: 10.1002/hed.23074
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of treatment and prognosis of sinonasal hemangiopericytoma

Abstract: BackgroundThis study was undertaken to determine the recurrence rate for open and endoscopic surgery and the clinical prognosis of this sinonasal tumor.MethodsA systematic review of individual cases of sinonasal hemangiopericytoma was performed. A total of 97 articles were included in the study and reviewed to extract the relevant information about each case.ResultsIn all, 194 cases of sinonasal hemangiopericytoma were identified. There were 53 recurrences (27.3%), 6 tumor‐related deaths (3.1%), and 4 cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 109 publications
3
75
0
4
Order By: Relevance
“…(4) With less than 200 cases of sinonasal hemangiopericytomas reported in the litera-ture, only limited assumptions can be made about the tumor. (10,11) This is another case of sinonasal hemangiopericytoma to add to the small but growing body of literature on this disease. Historically, open surgical methods for tumor extirpation have been considered as standard treatment, although endoscopic resection has increased in recent decades.…”
Section: Discussionmentioning
confidence: 95%
“…(4) With less than 200 cases of sinonasal hemangiopericytomas reported in the litera-ture, only limited assumptions can be made about the tumor. (10,11) This is another case of sinonasal hemangiopericytoma to add to the small but growing body of literature on this disease. Historically, open surgical methods for tumor extirpation have been considered as standard treatment, although endoscopic resection has increased in recent decades.…”
Section: Discussionmentioning
confidence: 95%
“…This presents as a nonhomogeneous soft tissue mass with bone erosion, necrosis, and early-stage intracranial growth [5]. Other highly vascular lesions are hemangioma (exceedingly rare in the nasal cavity and images may show a honey-comb appearance) and hemangiopericytomas (approximately 2.5% of all vascular sinonasal tumors, mostly heterogeneous, with cystic areas and signal-void vessels) [5,42,45,46]. …”
Section: Discussionmentioning
confidence: 99%
“…12,13 Few studies reports the use of radiotherapy and chemotherapy in cases of inoperable tumors, metastasis or palliative therapy. Limited study data showed that patients receiving radiotherapy following an incomplete surgical resection has lower rate of recurrence.…”
Section: -13mentioning
confidence: 99%
“…Limited study data showed that patients receiving radiotherapy following an incomplete surgical resection has lower rate of recurrence. 12 However, small number of data limits the assessment of its treatment efficacy.…”
Section: -13mentioning
confidence: 99%
See 1 more Smart Citation